Race and ethnicity expression in reproductive endocrinology and infertility research studies compared with other obstetrics and gynecology subspecialty studies - Anne Roshong, M.D; Kendal Rosalik, D.O; Samantha Carson, M.D; Laura Spilman, D.O; Jacqueline Luizzi, M.L.I.S., A.H.I.P; Torie Plowden, M.D; Bruce D. Pier, M.D (Elsevier, 2024)
Objective: To compare the percentage of patients per race and ethnicity group in the most cited reproductive endocrinology and infertility studies with the most cited studies in 3 other obstetrics and gynecology (OBGYN) subspecialties: gynecologic oncology, urogynecology (URO), and maternal-fetal medicine. Design: Retrospective cohort study. Setting: Not applicable. Patient(s): Patients previously recruited in research studies. Intervention(s): None. Main Outcome Measure(s): Expression of minorities in research studies. Result(s): Individual searches were conducted for the most cited articles in OBGYN subspecialties until 50 studies met the inclusion criteria for each OBGYN subspecialty. A total of 29,821,148 patients were included and compared between subspecialty and US Census data. Reproductive endocrinology and infertility studies had the highest percentage of White patients (80.5%), although URO studies had fewer Black patients (6.6%) compared with other subspecialties. Reproductive endocrinology and infertility studies had the lowest percentage of Hispanic patients (4.9%), yet more Asian patients were present in URO studies (3.3%) than in other subspecialties. Gynecologic oncology studies were most likely to have missing data in race expression (19.3%). Comparing study types, retrospective studies had the highest percentage of White patients (61.9%), although randomized controlled trials had the lowest expression of Hispanic patients (8.8%). Conclusion(s): Reproductive endocrinology and infertility studies featured the highest rates of White patients compared with other OBGYN subspecialty studies, although URO studies had the lowest rates of Black patients. Randomized controlled trials featured higher rates of White patients and lower levels of Hispanic patients compared with US Census data.